Class I PI3K regulatory subunits control differentiation of dendritic cell subsets and regulate Flt3L mediated signal transduction - Keyur Thummar; Chozha Vendan Rathinam (Scientific Reports)
Abstract Dendritic cells (DCs) play pivotal roles in initiating and shaping both innate and adaptive immune responses. The spatiotemporal expression of transcription factor networks and activation of specific signal transduction pathways determine the specification, distribution and differentiation of DC subsets. Even though pioneering studies have established indispensable roles for specific catalytic subunits (p110δ and p110γ) in immune cells, functions of the regulatory subunits, particularly of Class I PI3K, within the hematopoietic system remain incompletely understood. In the study presented here, we deleted the key regulatory subunits—p85α and p85β of the Class IA PI3K in hematopoietic cells and studied its impact on DC differentiation. Our studies identify that a deficiency of p85 causes increased differentiation of conventional DC (cDC) 2 and plasmacytoid DC (pDC) subsets in the spleen. On the other hand, DC numbers in the bone marrow (BM), thymus and lymph nodes were decreased in p85 mutant mice. Analysis of DC-specific progenitors and precursors indicated increased numbers in the BM and spleen of p85 deficient mice. In-vitro differentiation studies demonstrated augmented DC-differentiation capacities of p85 deficient BM cells in the presence of GM-CSF and Flt3L. BM chimera studies established that p85 deficiency affects DC development through cell intrinsic mechanisms. Molecular studies revealed increased proliferation of DCs and common DC progenitors (CDPs) in the absence of p85 and altered signal transduction pathways in p85 mutant DC subsets in response to Flt3L. In essence, data presented here, for the first time, unequivocally establish that the P85α subunit of class IA PI3Ks has an indispensable role in the development and maintenance of DCs.